2007
DOI: 10.1160/th07-01-0037
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor of activated T cells and early growth response-1 cooperate to mediate tissue factor gene induction by vascular endothelial growth factor in endothelial cells

Abstract: Endothelial progenitor cells (EPCs) have been implicated in vascular repair and found to be functionally impaired in patients with diabetes. We evaluated the effects of the anti-diabetic drug pioglitazone on human EPC function and the involvement of PPAR-gamma and TGF-beta1. EPCs in culture were characterized at day 7 by the development of colony-forming units (CFUs) and flow cytometry assessment of differentiation marker (DiI-ac-LDL/lectin, KDR and CD31). Adhesion on fibronectin and fibrinogen in flow was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 48 publications
(101 reference statements)
3
41
0
Order By: Relevance
“…FosB interacts with the DNA-binding complex AP1 and modulates nuclear gene transcription. 50 The transcription factor early growth response (Erg-1) has been shown to be involved in the tissue factor gene regulation, 51 and Etv5 is a member of the Ets transcription factor family. 44 Other cell signaling genes that are highly expressed in the SOD3 ÏȘ/ÏȘ lungs include the FGF receptor 3, which has been implicated in lymphatic vessel development 52 ; the Ras effector family member Rassf3, which can function as a tumor suppressor 53 ; and ARf3, a member of the small G-protein family that is involved in epithelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…FosB interacts with the DNA-binding complex AP1 and modulates nuclear gene transcription. 50 The transcription factor early growth response (Erg-1) has been shown to be involved in the tissue factor gene regulation, 51 and Etv5 is a member of the Ets transcription factor family. 44 Other cell signaling genes that are highly expressed in the SOD3 ÏȘ/ÏȘ lungs include the FGF receptor 3, which has been implicated in lymphatic vessel development 52 ; the Ras effector family member Rassf3, which can function as a tumor suppressor 53 ; and ARf3, a member of the small G-protein family that is involved in epithelial cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Activated PLCg1 cleaves PIP2 to generate DAG and IP3 and DAG can activate the RAF-MEK-ERK pathway via protein kinase C and IP3 via Ca 2ĂŸ release Ca 2ĂŸ -dependent enzymes, such as the serine/threonine phosphatase calcineurin, which dephosphorylates nuclear factor of activated T cells (NFAT) in endothelial cells (20)(21)(22). Expression of the PLCg1-R707Q mutant in HUVECs and HEK293 cells caused stronger phosphorylation of c-RAF, MEK, and ERK1/2 than PLCg1-WT (Fig.…”
Section: The R707q Mutation Activates Plcg1mentioning
confidence: 99%
“…Originally discovered as a potent and rapid inducer of vascular permeability (Vascular Permeability Factor, VPF) (Senger et al, 1983), it was then found to have a modest mitogenic effect on mature endothelial cells (Keck et al, 1989;Leung et al, 1989;Plouet et al, 1989) and finally it was shown to be an important participant in the regulation of EPC kinetics (Asahara et al, 1999;Olsson et al, 2006). Specifically, VEGF is believed to promote the mobilization of EPCs from the BM into the circulation by a) stimulating BM EPC proliferation b) providing a chemoattractive gradient for EPC migration towards the site of injury and c) modulating the BM-blood barrier, by increasing its permeability and modifying the expression of adhesion molecules (Asahara et al, 1999 Schabbauer et al, 2007). This is a tyrosine kinase containing in its cytoplasmic domain 19 tyrosine residues which are in part phosphorylated upon activation by receptor ligands and function as specific docking sites for molecules that initiate cytoplasmic signaling cascades (Olsson et al, 2006;Schabbauer et al, 2007).…”
Section: Inflammation-angiogenesis Cross-talkmentioning
confidence: 99%